Preparative liquid chromatography - Bidlingmeyer, Brian A. (Journal of chromatography library, 1987)
This volume provides a straightforward approach to isolation and purification problems with a thorough presentation of preparative LC strategy including the interrelationship between the input and output of the instrumentation, while keeping to an application focus. The book stresses the practical aspects of preparative scale separations from TLC isolations through various laboratory scale column separations to very large scale production. It also gives a thorough description of the performance parameters (e.g. throughput, separation quality, etc.) as a function of operational parameters (e.g. particle size, column size, solvent usage, etc.). Experts in the field have contributed a well balanced presentation of separation development strategies from preparative TLC to commercial preparative process with practical examples in a wide variety of application areas such as drugs, proteins, nucleotides, industrial extracts, organic chemicals, enantiomers, polymers, etc.